Impacts of water deficit in ecophysiological and spectral responses of coffee intercropped with woody species - Silveira, Helbert Rezende de Oliveira; Santos, Meline Oliveira; Silva, Vânia Aparecida; Venturin, Regis Pereira; Volpato, Margarete Marin Lordelo; Dantas, Mayara Fontes; Carvalho, Gladyston Rodrigues; Setotaw, Tesfahun Alemu; Moreira, Filipe Chaves; Barbosa, João Paulo Rodrigues Alves Delfino; Resende, Mário Lúcio Vilela de (Coffee Science - ISSN 1984-3909, 2016)
The aim of this study was to evaluate the effect of water stress in spectral and ecophysiological responses of coffee trees intercropped with woody species under water deficit. The “Catuaí Vermelho 99” was planted in monoculture and associated with the tree mahogany, teak and acrocarpo distributed in two spacings (9 x 13.6 and 18 x 13.6 m) line of coffee. Evaluations of growth of tree and coffee were performed 25 months after planting. The spectral and ecophysiological evaluations in coffee were held in four moments (June, August, September and December 2014). The acrocarpo presented greater height, crown and stem diameter. There were no differences between the growth of intercropping and monoculture coffee. The differences in water potential, spectral indices and ecophysiological were more evident in the early stages (August) and drought recovery (December). In August, the coffee monoculture showed higher Ψpd than intercropped coffee and was dicriminated by having positive scores and higher values of spectral indices NDVI, WBI, ARI1, CRI1, SIPI and FRI. On the other hand, in December, the largest Ψpd values were found in monoculture, intercropping with teak in both spacing and acrocarpo in greater spacing. However, this time, the highlight was the intercropping coffee with teak in wider spacing, which showed positive scores and higher values of US, potential photochemical efficiency of PSII and indexes (ARI1, CRI1 and FRI). The intercropping with teak in greater spacing has a positive impact on the spectral and ecophysiological coffee’s responses after the drought.